2006
DOI: 10.1017/s0952523806233352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motion and configural complexity on color transparency perception

Abstract: We tested whether motion and configural complexity affect perceived transparency. A series of five coherent chromatic transformations in color space was applied across a figure: translation, convergence, shear, divergence and rotation. The stimuli consisted of a bipartite or a checkerboard configuration (10 x 10 degrees), with a central static or moving overlay (5 x 5 degrees). Three different luminance conditions (the plane of chromatic transformation oriented toward higher, lower, or equal luminances) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…In pointing out the role of certain shape changes in promoting impressions of transparency, particularly for shadows, Metzger (1936) mentions in a footnote that the law of common fate would add a contribution to transparency perception in a movie, but without presenting details of the conditions or evidence, and it is highly unlikely that he was imagining a condition where common fate conflicts with other cues that are voting against transparency. The role we demonstrate for motion defined common fate explains motion enhancing effects in previous studies ( D'Zmura et al, 2000 ; Falkenberg & Faul, 2019 ; Gerardin et al, 2006 ; Khang & Zaidi, 2002a ), but goes beyond them in showing that common fate can override the information provided by junctions, which are otherwise quite powerful factors ( Anderson, 1997 ). In fact, by replacing ellipses with rectangles in the overlaid surface ( Figure 9 ), we demonstrate that, because of common fate, transparency can still be seen despite junction, color, and pattern information all being otherwise incompatible with transparency.…”
Section: Discussionsupporting
confidence: 56%
“…In pointing out the role of certain shape changes in promoting impressions of transparency, particularly for shadows, Metzger (1936) mentions in a footnote that the law of common fate would add a contribution to transparency perception in a movie, but without presenting details of the conditions or evidence, and it is highly unlikely that he was imagining a condition where common fate conflicts with other cues that are voting against transparency. The role we demonstrate for motion defined common fate explains motion enhancing effects in previous studies ( D'Zmura et al, 2000 ; Falkenberg & Faul, 2019 ; Gerardin et al, 2006 ; Khang & Zaidi, 2002a ), but goes beyond them in showing that common fate can override the information provided by junctions, which are otherwise quite powerful factors ( Anderson, 1997 ). In fact, by replacing ellipses with rectangles in the overlaid surface ( Figure 9 ), we demonstrate that, because of common fate, transparency can still be seen despite junction, color, and pattern information all being otherwise incompatible with transparency.…”
Section: Discussionsupporting
confidence: 56%
“…Gerardin , Roud, Süsstrunk, and Knoblauch (2006) found that the configural complexity of the background figure 1 in Gerbino, 2015, as well as those in panels (c) and (d), are identical with regard to their luminance relations and also fulfill the topological requirements according to Kanizsa (1979), and yet the impression of transparency is clearly weakened in (b) and (d). In panel (a), the impression of a transparent dark bar in front of a white cross is evoked.…”
Section: Texture Densitymentioning
confidence: 89%
“…Moving filters were often used with the intention to support the decomposition (D'Zmura, Khang & Zaidi, 2002b;Khang & Zaidi, 2004;Faul & Falkenberg, 2015) but the effectiveness of this manipulation was not tested. Gerardin et al (2006) observed almost 100% correct transparency classification in a condition with moving filters. Apart from an effect due to a boosted decomposition, motion could also improve constancy for other reasons: As noted by Khang and Zaidi (2002b), a moving filter generates a larger sample of overlaid background colors than a static filter, which makes it less probable that single surfaces cause a color bias.…”
Section: Motionmentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, it should be noted that all of the experiments described herein utilized moving images to assess the perception of chromatic transparency. Gerardin, Roud, Süsstrunk, and Knoblauch (2006) recently showed that motion can cause otherwise non-transparent surfaces to appear transparent, which suggests that the use of motion in our displays could have introduced a confound in assessing the conditions of perceiving transparency in static displays. However, as can be seen directly by viewing both the static and moving versions of our displays, motion never caused a non-transparent display to appear transparent in our stimuli; it merely facilitated the judgment of the color of the target disk.…”
Section: Relationship To Previous Workmentioning
confidence: 99%